Interleukin‐6 Family of Cytokines in Crevicular Fluid of Renal Transplant Recipients With and Without Cyclosporine A–Induced Gingival Overgrowth. Issue 9 (1st September 2015) - Gürkan, Ali; Becerik, Sema; Öztürk, Veli Özgen; Atmaca, Harika; Atilla, Gül; Emingil, Gülnur
Abstract : Background: Interleukin (IL)‐6 family of cytokines, including IL‐6, oncostatin M (OSM), leukemia inhibitory factor (LIF), and IL‐11, have fibrogenic features. The current study determines gingival crevicular fluid (GCF) levels of fibrosis‐related IL‐6–type cytokines in cyclosporine A (CsA)–induced gingival overgrowth (GO). Methods: Eighty non‐smokers were included (40 CsA‐medicated renal transplant patients with GO [GO+ ; n= 20] or without GO [GO−; n= 20], 20 individuals with gingivitis, and 20 healthy participants). Probing depth and plaque, papilla bleeding, and hyperplastic index scores were recorded. GCF samples were obtained from the mesio‐buccal aspects of two teeth. GCF IL‐6, IL‐1β, OSM, LIF, and IL‐11 levels were analyzed by enzyme‐linked immunosorbent assay. Results: The GO+ and GO− groups had higher IL‐6 total amounts than the healthy group ( P <0.008). IL‐1β total amounts in the GO+ group were significantly higher than in both the healthy and GO− groups ( P <0.008). OSM total amount was elevated in the GO+ and GO− groups compared with both the gingivitis and healthy groups ( P <0.008). All groups had similar LIF and IL‐11 total amounts ( P >0.008). Moderate positive correlations were detected among IL‐6, IL‐1β, OSM, and IL‐11 total amount in GCF and clinical parameters ( P <0.05). Conclusions: IL‐6 and OSM increases in GCF as a result of CsA usage or an immunosuppressed state irrespective of the severity of inflammation and the presence of GO. The IL‐6 family of cytokines might not be directly involved in biologic mechanisms associated with CsA‐induced GO. Lack of an association between assessed IL‐6 cytokines and CsA‐induced GO might indicate distinct effects of these cytokines on fibrotic changes of different tissues.